2016
DOI: 10.1155/2016/2640730
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Morbidity and Mortality of Perforated Peptic Ulcer: Retrospective Cohort Study of Risk Factors among Black Africans in Côte d’Ivoire

Abstract: Introduction. Surgical treatment of perforated peptic ulcer (PPU) is a challenge for surgeons in Africa. Aim. To determine risk factors of postoperative complications or mortality among black Ivoirian patients with PPU. Methods. All 161 patients (median age = 34 years, 90.7 male) operated on for PPU in the visceral and general surgery unit were enrolled in a retrospective cohort study. Variables were studied with Kaplan Meier and Cox proportional hazard models. Results. Among 161 patients operated on for PPU, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
6
27
1
Order By: Relevance
“…Two third (66.6%) of the deaths occurred on patients who presented within 24 hours after the onset of symptoms. Similar studies done in Turkey, Singapore and Ivory Coast also showed presentation after 24 hours of the onset of symptoms increased both post-operative complications and mortality (10,11,12).…”
Section: Discussionsupporting
confidence: 72%
“…Two third (66.6%) of the deaths occurred on patients who presented within 24 hours after the onset of symptoms. Similar studies done in Turkey, Singapore and Ivory Coast also showed presentation after 24 hours of the onset of symptoms increased both post-operative complications and mortality (10,11,12).…”
Section: Discussionsupporting
confidence: 72%
“…The rate of IHDs of 36·8 per cent in the present study was similar to that in an earlier study at a well staffed teaching hospital in Nigeria, where 50 per cent of patients waited over 24 h, and 16 per cent waited more than 48 h for operative intervention. At a regional hospital in Uganda 48 per cent of 31 operations were delayed (median delay 14·8 h), and in the Ivory Coast 86 per cent of patients had a delay of more than 24 h from symptom onset to surgery, with more than 36 per cent waiting over 48 h. Delays were defined in the present study as longer than 24 h. Most surgeons would agree that this is too long to wait for emergency care, and several other studies, especially in LMICs, have used this definition, although some high‐income countries (HICs) have used shorter times. Future research to measure specific time intervals, including time to decision to operate, time to diagnostic studies and exact times to procedures, should clarify the length of an acceptable in‐hospital wait.…”
Section: Discussionmentioning
confidence: 85%
“…IHDs have been associated with worse outcomes in both HICs and LMICs 7,10 . The overall mortality rate in the present study of 11⋅8 per cent was similar to rates of 10-19 per cent seen in other series 10,15,24,25 of abdominal operations in the region. In HICs, delays are often considered to have shorter intervals of less than 6 or 12 h 7,8,22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations